2022
DOI: 10.1186/s12985-022-01783-5
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of SARS-CoV-2 evading host antiviral innate immunity

Abstract: The newly identified Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has resulted in a global health emergency (COVID-19) because of its rapid spread and high mortality. Since the virus epidemic, many pathogenic mechanisms have been revealed, and virus-related vaccines have been successfully developed and applied in clinical practice. However, the pandemic is still developing, and new mutations are still emerging. Virus pathogenicity is closely related to the immune status of the host. As innate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 107 publications
0
33
0
2
Order By: Relevance
“…NSP8 initiates the synthesis of complementary short oligonucleotides and provides RNA primers required by NSP12 during viral replication and transcription (Imbert et al, 2006). It has been suggested that NSP8, being engaged in specific cytoplasmic foci, can form complexes with NSP7, NSP9, and NSP10 (Zhai et al, 2005;Achour, 2021) and suppress protein integration into cytoplasmic membrane thereby mitigate the interferon response of host cells (Banerjee et al, 2020;Gu et al, 2022). Recent studies highlighted the possibility of NSP8 as an antigenic target of SARS-CoV-2 (Ahmad et al, 2020;Ong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…NSP8 initiates the synthesis of complementary short oligonucleotides and provides RNA primers required by NSP12 during viral replication and transcription (Imbert et al, 2006). It has been suggested that NSP8, being engaged in specific cytoplasmic foci, can form complexes with NSP7, NSP9, and NSP10 (Zhai et al, 2005;Achour, 2021) and suppress protein integration into cytoplasmic membrane thereby mitigate the interferon response of host cells (Banerjee et al, 2020;Gu et al, 2022). Recent studies highlighted the possibility of NSP8 as an antigenic target of SARS-CoV-2 (Ahmad et al, 2020;Ong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our observed decrease of ACE2 levels due to ageing has been previously described and it was postulated as one of the causes for the increased mortality rate in elder patients ( Xie et al, 2006 ; Berni Canani et al, 2021 ). However, other authors have hypothesized that COVID-19 susceptibility in elderly can be related to the increase of ACE2 expression ( Narula et al, 2020 ; Gu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…One is to block binding to ISRE and GAS by inhibiting STAT1 nuclear translocation. For the CoVs, SARS-CoV-2 and SARS-CoV ORF6 inhibit ISRE promoter activation by blocking STAT1 nuclear translocation but not phosphorylation [ 29 , 46 , 47 ]. However, in IBV-infected Vero cells, IBV-mediated inhibition of STAT1 nuclear translocation after IFN-β treatment is independent of accessory proteins [ 35 ].…”
Section: Discussionmentioning
confidence: 99%